Lithium battery composite negative electrode material and preparation method thereof
By using a composite material of Fe-Ni bimetallic organic frame and sodium alginate modified nano-silicon powder in lithium-ion batteries, the problem of volume expansion and cycle stability of the negative electrode of lithium-ion batteries is solved, and high specific capacity and good electricity are achieved Chemical properties.
Patent Information
- Application Number
- CN202411371685.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-29
AI Technical Summary
Existing lithium-ion battery anode materials, especially graphite materials, cannot meet the high requirements of battery energy density and use stability. As an alternative material, volume expansion of silicon during lithium-ion insertion/detachment leads to rapid attenuation of battery capacity and relatively long cycle life. Difference.
The composite negative electrode material prepared by a metal Fe-Ni bimetallic organic frame and sodium alginate modified nano-silicon powder form a loose porous structure, and the sodium alginate modified nano-silicon particles are evenly dispersed in the iron-nickel organic metal frame-based porous carbon material Electrochemical stability and conductivity are enhanced in the pores.
It improves the cycle stability and rate performance of lithium-ion batteries, reduces the volume expansion of the silicon negative electrode, extends the cycle life of the battery, and improves the diffusion rate of lithium ions and the overall performance of the battery.
Smart Images

Figure CN119252893A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a lithium battery composite negative electrode material and a preparation method thereof. Background Art
[0002] With the rapid economic development of my country, the existing energy system can no longer meet the demand. The consumption of fossil fuels is irreversible and has also brought immeasurable environmental problems. The widespread use of electric energy has driven the development of lithium-ion batteries. The negative electrodes of current commercial lithium-ion batteries mainly use various graphite materials. Although the preparation technology is mature, the maximum capacity can only reach its theoretical specific capacity value (372 mA·h / g), which is difficult to meet the high requirements for battery energy density and stability of use. Therefore, the development of high-performance lithium-ion batteries is a top priority.
[0003] As a new type of negative electrode material for lithium batteries, silicon has become the focus of researchers due to its high theoretical specific capacity (4200mAh / g). However, using it directly as a negative electrode material cannot highlight the high capacity advantage, mainly because when lithium ions are inserted into / extracted from the silicon unit cell, it will cause severe volume expansion, and then cracks will appear on the electrode surface, resulting in rapid attenuation of battery capacity and poor cycle life.
[0004] In order to solve the above problems, silicon-carbon composite materials have attracted more and more attention from researchers. Silicon materials provide high specific capacity, while carbon materials have excellent electrochemical and structural stability, good conductivity, and almost no volume change during lithiation, keeping the electrode intact, which can effectively solve the problem of volume expansion of silicon negative electrode during lithium-ion battery deintercalation. Therefore, how to prepare high-performance lithium battery composite negative electrode materials and improve the electrochemical stability of composite materials is an urgent problem to be solved in this field. Summary of the invention
[0005] The purpose of the present invention is to provide a lithium battery composite negative electrode material and a preparation method thereof. The negative electrode material is a lithium battery negative electrode material prepared with a metal Fe-Ni bimetallic organic framework and sodium alginate modified nano silicon powder as raw materials. The material has a loose porous structure and can effectively solve the problem of volume expansion of the silicon negative electrode during the deintercalation process of the lithium ion battery. The nano silicon particles modified by sodium alginate are uniformly dispersed in the pores of the iron-nickel organic metal framework-based porous carbon material to form a stable composite material structure. This structure can not only utilize the high lithium storage capacity of silicon, but also give play to the excellent conductivity and structural stability of the porous carbon material, and has good rate performance and cycle stability.
[0006] In order to achieve the above technical objectives, the technical solution adopted by the present invention is: A method for preparing a composite negative electrode material for a lithium battery comprises the following steps: (1) Dissolve triethylenediamine and terephthalic acid in DMF, stir evenly, add FeCl2·4H2O and NiCl2·6H2O to the uniform solution, stir magnetically for 3 h, transfer to a polytetrafluoroethylene hydrothermal reactor, react at 150°C for 24 h, cool naturally to room temperature, wash the obtained solid product with DMF and anhydrous ethanol by centrifugation for 3-5 times, and dry it in a vacuum drying oven to obtain a Fe-Ni-MOF substrate; (2) Add 0.5 g of sodium alginate to 100 ml of 1 mol / L NaCl solution, stir and dissolve completely to obtain solution A; add 2 g of nano-silicon powder to 100 ml of deionized water, disperse evenly by ultrasonication and mix evenly with solution A, react for 2-3 hours under magnetic stirring, separate by centrifugation to obtain a solid product, wash with deionized water for several times, and dry in an oven to obtain a sodium alginate modified nano-silicon material; (3) The Fe-Ni-MOF substrate is mixed with the sodium alginate modified nano-silicon material, and after mechanical ball milling for 1 hour, the mixture is transferred into a tubular furnace, argon is introduced as a protective gas, high-temperature calcination is performed, and natural cooling and grinding are performed to obtain a lithium battery composite negative electrode material.
[0007] Preferably, in step (1), the molar ratio of triethylenediamine, terephthalic acid, FeCl2·4H2O, and NiCl2·6H2O is 15:15:4:1; and the concentration of triethylenediamine in the DMF solution is 0.05 mol / L.
[0008] Preferably, the vacuum drying temperature in step (1) is 80° C. and the time is 12 h.
[0009] Preferably, in step (2), the oven drying temperature is 60° C. and the time is 10 h.
[0010] Preferably, in step (3), the mass ratio of the Fe-Ni-MOF substrate to the sodium alginate modified nano-silicon material is 0.3-0.8:1.
[0011] Preferably, the high temperature calcination method in step (3) is as follows: heating to 200°C at a rate of 3°C / min, keeping the temperature for 1-2 hours, adjusting the heating rate to 5°C / min to 800°C, and keeping the temperature for 2-3 hours.
[0012] The present invention adopts the lithium battery composite negative electrode material prepared by the above method, and its specific use method is: the negative electrode material prepared by the present invention is fully ground and then ground and stirred with conductive black and binder in a mass ratio of 8:1:1 to form a uniformly dispersed slurry, and then coated on a copper foil with an I-shaped scraper, and the slurry thickness is 75μm. Dry in a vacuum drying oven at 60°C for 12 hours, take out and cut into discs with a diameter of 12 mm on a slicer and press at a pressure of 6 MPa to obtain a lithium battery negative electrode. The lithium battery negative electrode material has good electrochemical properties and improves the cycle stability and rate performance of the battery. At the same time, the special porous structure of the prepared composite material is more conducive to the penetration of the electrolyte into the electrode material, shortens the transmission path of electrons and lithium ions, and improves the diffusion rate of lithium ions and the cycle performance of the battery.
[0013] Compared with the prior art, the present invention has the following beneficial effects: 1) The present invention rationally designs and synthesizes Fe-Ni bimetallic organic framework materials as carbon materials, and rationally adjusts the ratio of Fe-Ni to produce porous materials with higher porosity. The rich pore structure and active sites inside the material are conducive to the embedding and extraction of lithium ions, providing a transmission channel for a large number of ions and electrons. The introduction of iron-nickel bimetallic further enhances the transmission performance, so that the material can quickly respond to current changes during the charge and discharge process and maintain good structural stability during the charge and discharge process.
[0014] 2) At the same time, the present invention uses nano silicon powder modified by sodium alginate as silicon-based material. The addition of sodium alginate can interact with the surface of nano silicon powder through the hydrophilic groups carboxyl and hydroxyl on its molecular chain, reduce surface energy, and significantly improve the cycle stability of nano silicon powder. It is coated on the surface of silicon particles, which can effectively prevent the volume expansion of silicon during the charging and discharging process and reduce structural damage; the nano silicon powder modified by sodium alginate and iron-nickel MOFs support each other in structure to form a more stable electrode structure, which helps to resist mechanical stress during charging and discharging and reduce the pulverization and shedding of electrode materials; the protective layer formed by sodium alginate on the surface of silicon particles can also prevent silicon from directly contacting the electrolyte, reduce the occurrence of side reactions, and improve the stability of the interface. The porous structure of iron-nickel MOFs also provides more channels for the penetration of electrolyte, which helps to form a more stable SEI film.
[0015] 3) The lithium battery composite negative electrode material prepared by the present invention has excellent cycle stability, high specific capacity, and small capacity loss after cyclic discharge, and has a good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1The scanning electron microscope images of the electrode materials obtained in Example 3 and Comparative Example 1 of the present invention, wherein a is the SEM image of Example 3, b is a partial enlarged image of the SEM image of Example 3, and c is the SEM image of Comparative Example 1; Figure 2 This is a graph showing the electrochemical impedance test results of the electrode materials obtained in Example 3, Comparative Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0017] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto. Example
[0018] A method for preparing a composite negative electrode material for a lithium battery comprises the following steps: (1) Dissolve triethylenediamine and terephthalic acid in DMF and stir evenly. Add FeCl2·4H2O and NiCl2·6H2O to the uniform solution. Stir magnetically for 3 h and transfer into a polytetrafluoroethylene hydrothermal reactor. React at 150°C for 24 h and cool naturally to room temperature. Wash the obtained solid product three times with DMF and anhydrous ethanol by centrifugation and dry it in a vacuum drying oven at 80°C for 12 h to obtain a Fe-Ni-MOF substrate. The molar ratio of triethylenediamine, terephthalic acid, FeCl2·4H2O and NiCl2·6H2O is 15:15:4:1. The concentration of triethylenediamine in the DMF solution is 0.05 mol / L.
[0019] (2) Take 0.5g of sodium alginate and add it to 100ml of 1mol / L NaCl solution, stir and dissolve it completely to obtain solution A; take 2g of nano-silicon powder and add it to 100ml of deionized water, disperse it evenly by ultrasonication and mix it evenly with solution A, react it under magnetic stirring for 3h, centrifuge and obtain a solid product, wash it with deionized water for several times, and dry it in an oven at 60℃ for 10h to obtain a sodium alginate modified nano-silicon material; (3) The Fe-Ni-MOF substrate and the sodium alginate modified nano-silicon material were mixed, and after mechanical ball milling for 1 hour, the mixture was transferred to a tubular furnace, argon gas was introduced as a protective gas, high-temperature calcined, naturally cooled and ground to obtain a lithium battery composite negative electrode material; the mass ratio of the Fe-Ni-MOF substrate to the sodium alginate modified nano-silicon material was 0.3:1; the high-temperature calcination method was specifically as follows: heating to 200°C at a rate of 3°C / min, keeping warm for 2 hours, adjusting the heating rate to 5°C / min to 800°C, and keeping warm for 2 hours. Example
[0020] A method for preparing a composite negative electrode material for a lithium battery comprises the following steps: (1) Dissolve triethylenediamine and terephthalic acid in DMF and stir evenly. Add FeCl2·4H2O and NiCl2·6H2O to the even solution. Stir magnetically for 3 h and transfer into a polytetrafluoroethylene hydrothermal reactor. React at 150°C for 24 h and cool naturally to room temperature. Wash the obtained solid product by centrifugation for 5 times with DMF and anhydrous ethanol and dry it in a vacuum drying oven at 80°C for 12 h to obtain a Fe-Ni-MOF substrate. The molar ratio of triethylenediamine, terephthalic acid, FeCl2·4H2O and NiCl2·6H2O is 15:15:4:1. The concentration of triethylenediamine in the DMF solution is 0.05 mol / L.
[0021] (2) Take 0.5g of sodium alginate and add it to 100ml of 1mol / L NaCl solution, stir and dissolve it completely to obtain solution A; take 2g of nano-silicon powder and add it to 100ml of deionized water, disperse it evenly by ultrasonication and mix it evenly with solution A, react it under magnetic stirring for 2h, centrifuge and obtain a solid product, wash it with deionized water for several times, and dry it in an oven at 60℃ for 10h to obtain a sodium alginate modified nano-silicon material; (3) The Fe-Ni-MOF substrate and the sodium alginate modified nano-silicon material were mixed, and after mechanical ball milling for 1 hour, the mixture was transferred to a tubular furnace, argon gas was introduced as a protective gas, high-temperature calcined, naturally cooled and ground to obtain a lithium battery composite negative electrode material; the mass ratio of the Fe-Ni-MOF substrate to the sodium alginate modified nano-silicon material was 0.5:1; the high-temperature calcination method was specifically as follows: heating to 200°C at a rate of 3°C / min, keeping warm for 1 hour, adjusting the heating rate to 5°C / min to 800°C, and keeping warm for 3 hours. Example
[0022] A method for preparing a composite negative electrode material for a lithium battery comprises the following steps: (1) Dissolve triethylenediamine and terephthalic acid in DMF and stir evenly. Add FeCl2·4H2O and NiCl2·6H2O to the even solution. Stir magnetically for 3 h and transfer into a polytetrafluoroethylene hydrothermal reactor. React at 150°C for 24 h and cool naturally to room temperature. Wash the obtained solid product by centrifugation for 5 times with DMF and anhydrous ethanol and dry it in a vacuum drying oven at 80°C for 12 h to obtain a Fe-Ni-MOF substrate. The molar ratio of triethylenediamine, terephthalic acid, FeCl2·4H2O and NiCl2·6H2O is 15:15:4:1. The concentration of triethylenediamine in the DMF solution is 0.05 mol / L.
[0023] (2) Take 0.5g of sodium alginate and add it to 100ml of 1mol / L NaCl solution, stir and dissolve it completely to obtain solution A; take 2g of nano-silicon powder and add it to 100ml of deionized water, disperse it evenly by ultrasonication and mix it evenly with solution A, react it under magnetic stirring for 3h, centrifuge and obtain a solid product, wash it with deionized water for several times, and dry it in an oven at 60℃ for 10h to obtain a sodium alginate modified nano-silicon material; (3) The Fe-Ni-MOF substrate and the sodium alginate modified nano-silicon material were mixed, and after mechanical ball milling for 1 hour, the mixture was transferred to a tubular furnace, argon gas was introduced as a protective gas, high-temperature calcined, naturally cooled and ground to obtain a lithium battery composite negative electrode material; the mass ratio of the Fe-Ni-MOF substrate to the sodium alginate modified nano-silicon material was 0.8:1; the high-temperature calcination method was specifically as follows: heating to 200°C at a rate of 3°C / min, keeping warm for 1 hour, adjusting the heating rate to 5°C / min to 800°C, and keeping warm for 2 hours.
[0024] A method for preparing a composite negative electrode material for a lithium battery comprises the following steps: (1) Dissolve triethylenediamine and terephthalic acid in DMF, stir evenly, add FeCl2·4H2O to the even solution, stir magnetically for 3 h, transfer into a polytetrafluoroethylene hydrothermal reactor, react at 150°C for 24 h, cool naturally to room temperature, wash the obtained solid product by centrifugation for 3-5 times with DMF and anhydrous ethanol, dry it in a vacuum drying oven at 80°C for 12 h, and obtain a Fe-MOF substrate; wherein the molar ratio of triethylenediamine, terephthalic acid, and FeCl2·4H2O is 15:15:4; and the concentration of triethylenediamine in the DMF solution is 0.05 mol / L.
[0025] (2) Take 0.5g of sodium alginate and add it to 100ml of 1mol / L NaCl solution, stir and dissolve it completely to obtain solution A; take 2g of nano-silicon powder and add it to 100ml of deionized water, disperse it evenly by ultrasonication and mix it evenly with solution A, react it under magnetic stirring for 3h, centrifuge and obtain a solid product, wash it with deionized water for several times, and dry it in an oven at 60℃ for 10h to obtain a sodium alginate modified nano-silicon material; (3) The Fe-Ni-MOF substrate and the sodium alginate modified nano-silicon material were mixed, and after mechanical ball milling for 1 hour, the mixture was transferred to a tubular furnace, argon gas was introduced as a protective gas, high-temperature calcined, naturally cooled and ground to obtain a lithium battery composite negative electrode material; the mass ratio of the Fe-Ni-MOF substrate to the sodium alginate modified nano-silicon material was 0.8:1; the high-temperature calcination method was specifically as follows: heating to 200°C at a rate of 3°C / min, keeping warm for 1 hour, adjusting the heating rate to 5°C / min to 800°C, and keeping warm for 2 hours.
[0026] This comparative example is the same as Example 3 except that NiCl2·6H2O is not added in step (1).
[0027] A method for preparing a composite negative electrode material for a lithium battery comprises the following steps: (1) Dissolve triethylenediamine and terephthalic acid in DMF and stir evenly. Add FeCl2·4H2O and NiCl2·6H2O to the even solution. Stir magnetically for 3 h and transfer into a polytetrafluoroethylene hydrothermal reactor. React at 150°C for 24 h and cool naturally to room temperature. Wash the obtained solid product by centrifugation for 5 times with DMF and anhydrous ethanol and dry it in a vacuum drying oven at 80°C for 12 h to obtain a Fe-Ni-MOF substrate. The molar ratio of triethylenediamine, terephthalic acid, FeCl2·4H2O and NiCl2·6H2O is 15:15:4:1. The concentration of triethylenediamine in the DMF solution is 0.05 mol / L.
[0028] (2) The Fe-Ni-MOF substrate and nano-silicon powder were mixed, and after mechanical ball milling for 1 hour, the mixture was transferred to a tubular furnace, argon was introduced as a protective gas, high-temperature calcination was performed, and the mixture was naturally cooled and ground to obtain a lithium battery composite negative electrode material; the mass ratio of the Fe-Ni-MOF substrate to the nano-silicon powder was 0.8:1; the high-temperature calcination method was specifically as follows: heating to 200°C at a rate of 3°C / min, keeping warm for 1 hour, adjusting the heating rate to 5°C / min to 800°C, and keeping warm for 2 hours.
[0029] This comparative example is the same as Example 3 except that unmodified nano silicon powder is directly used.
[0030] Performance Testing The lithium battery composite negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to electrochemical performance tests, and the specific steps were as follows: the negative electrode material prepared in the present invention was fully ground and then ground and stirred with acetylene black and sodium alginate in a mass ratio of 8:1:1 to form a uniformly dispersed slurry, and then coated on a copper foil with an I-shaped scraper, with a slurry thickness of 75 μm. Dry in a vacuum drying oven at 60°C for 12 h, take out and cut into discs with a diameter of 12 mm on a slicer and press at a pressure of 6 MPa to obtain a lithium battery negative electrode. After weighing and marking, quickly transfer to an argon atmosphere glove box to assemble a CR-2032 button battery, the counter electrode is a metal lithium sheet, the diaphragm model is Celgard 2400, and the diameter is 19 mm. After the assembly is left to stand for 12 hours, various electrochemical performance tests are performed. The battery charge and discharge test system is used to perform cyclic charge and discharge tests at a set current density, with a voltage range of 0.01~2.00 V. First, the battery was activated for 3 cycles at a current density of 50 mA / g, and then a long cycle test was performed at a current density of 100 mA / g. The specific test results are shown in Table 1.
[0031] Table 1 Performance test results ; It can be seen from the above data that the lithium battery composite negative electrode material prepared by the present invention has good electrochemical properties, high discharge specific capacity, good conductivity and cycle performance, which shows that the material of the present invention has a loose porous structure, which can effectively solve the problem of volume expansion of the silicon negative electrode during the deintercalation process of the lithium ion battery. The nano-silicon particles modified by sodium alginate are uniformly dispersed in the pores of the iron-nickel organic metal framework-based porous carbon material ( Figure 1 ), forming a stable composite material structure. This structure can not only utilize the high lithium storage capacity of silicon, but also give full play to the excellent conductivity and structural stability of porous carbon materials, and has good rate performance and cycle stability.
[0032] The lithium battery composite negative electrode materials prepared in Example 3, Comparative Example 1 and Comparative Example 2 were selected and AC impedance test was performed using an electrochemical analyzer. The electrochemical impedance test parameters were as follows: the test frequency range was: 0.1×10 -6 ~1×10 6 Hz. EIS spectrum and corresponding fitting circuit are shown in Figure 2 As shown. In the fitting circuit diagram, R s , R ct are electrolyte resistance and charge transfer resistance respectively, CPE1 is the constant phase angle element related to the interface resistance, and W0 is the element of Warburg resistance, where R ct It can reflect the difficulty of the charge transfer process at the electrode / electrolyte interface. Figure 2It can be seen that the impedance R ct The impedance values are significantly lower than those of Comparative Examples 1 and 2, which indicates that the introduction of the iron-nickel bimetallic and the synergistic effect of diatomaceous earth-modified nano-silicon powder in the electrode material prepared by the present invention further enhance the conductivity of the material, and the material has good electrochemical performance.
[0033] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
Claims
1. A method for preparing a composite negative electrode material for a lithium battery, characterized in that: It includes the following steps: (1) Dissolve triethylenediamine and terephthalic acid in DMF, stir evenly, add FeCl2·4H2O and NiCl2·6H2O to the uniform solution, stir magnetically for 3 h, transfer to a polytetrafluoroethylene hydrothermal reactor, react at 150°C for 24 h, cool naturally to room temperature, wash the obtained solid product with DMF and anhydrous ethanol by centrifugation for 3-5 times, and dry it in a vacuum drying oven to obtain a Fe-Ni-MOF substrate; (2) Add 0.5 g of sodium alginate to 100 ml of 1 mol / L NaCl solution, stir and dissolve completely to obtain solution A; add 2 g of nano-silicon powder to 100 ml of deionized water, disperse evenly by ultrasonication and mix evenly with solution A, react for 2-3 hours under magnetic stirring, separate by centrifugation to obtain a solid product, wash with deionized water for several times, and dry in an oven to obtain a sodium alginate modified nano-silicon material; (3) The Fe-Ni-MOF substrate is mixed with the sodium alginate modified nano-silicon material, and after mechanical ball milling for 1 hour, the mixture is transferred into a tubular furnace, argon is introduced as a protective gas, high-temperature calcination is performed, and natural cooling and grinding are performed to obtain a lithium battery composite negative electrode material.
2. The method for preparing a composite negative electrode material for a lithium battery according to claim 1, characterized in that: In the step (1), the molar ratio of triethylenediamine, terephthalic acid, FeCl2·4H2O and NiCl2·6H2O is 15:15:4:1; and the concentration of triethylenediamine in the DMF solution is 0.05 mol / L.
3. The method for preparing a composite negative electrode material for a lithium battery according to claim 1, characterized in that: The vacuum drying temperature in step (1) is 80° C. and the time is 12 h.
4. The method for preparing a composite negative electrode material for a lithium battery according to claim 1, characterized in that: In step (2), the oven drying temperature is 60° C. and the time is 10 h.
5. The method for preparing a composite negative electrode material for a lithium battery according to claim 1, characterized in that: In the step (3), the mass ratio of the Fe-Ni-MOF substrate to the sodium alginate modified nano-silicon material is 0.3-0.8:
1.
6. The method for preparing a composite negative electrode material for a lithium battery according to claim 1, characterized in that: The high temperature calcination method in step (3) is specifically as follows: heating to 200°C at a rate of 3°C / min, keeping the temperature for 1-2 hours, adjusting the heating rate to 5°C / min to 800°C, and keeping the temperature for 2-3 hours.
7. A lithium battery composite negative electrode material prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Iron-based double-ligand metal organic framework material capable of preferentially adsorbing ethane as well as preparation method and application of iron-based double-ligand metal organic framework material
CN108329484A
Lithium-ion-battery composite material and preparing method of composite electrode of lithium ion battery
CN108565406A
Carbon coated transition metal nano-composite material and preparation method and application thereof
CN109304201A
Preparation of nickel-iron alloy / nitrogen-doped carbon electrocatalyst and application of nickel-iron alloy / nitrogen-doped carbon electrocatalyst in rechargeable zinc-air battery
CN110071299A
Silicon-carbon-metal composite negative electrode material and preparation method thereof
CN115064687A
